2022
DOI: 10.3390/antiox11081530
|View full text |Cite
|
Sign up to set email alerts
|

R- Is Superior to S-Form of α-Lipoic Acid in Anti-Inflammatory and Antioxidant Effects in Laying Hens

Abstract: The development of single enantiomers with high efficiency and low toxic activity has become a hot spot for the development and application of drugs and active additives. The aim of the present study was to investigate the effectiveness of the application of α-lipoic acid with a different optical rotation to alleviate the inflammation response and oxidative stress induced by oxidized fish oil in laying hens. Sixty-four 124-week-old Peking Red laying hens were randomly allocated to four groups with eight replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…R(+)-α-lipoic acid is generally recognized to exhibit superior activity compared to S(-)-α-lipoic acid [ 2 , 3 , 4 , 5 , 6 ], even as α-lipoic acid is usually marketed as a racemic mixture containing both enantiomers. To date, the extent to which each enantiomer contributes to α-lipoic acid pharmacological and toxicological effects is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…R(+)-α-lipoic acid is generally recognized to exhibit superior activity compared to S(-)-α-lipoic acid [ 2 , 3 , 4 , 5 , 6 ], even as α-lipoic acid is usually marketed as a racemic mixture containing both enantiomers. To date, the extent to which each enantiomer contributes to α-lipoic acid pharmacological and toxicological effects is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the extent to which each enantiomer contributes to α-lipoic acid pharmacological and toxicological effects is not fully understood. While it was proposed that S(-)-α-lipoic acid does not exhibit significant biological side effects [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], some studies indicated that it could potentially hinder the activity of the R(-)-enantiomer [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation